Qr-code dan pembelajaran kosakata: sentuhan digital dalam pembelajaran Bahasa Jerman - Bukhori, Herri Akhmad; Rofi'ah, Rofi'ah (2021)
Digital media in the era of the industrial revolution 4.0 plays an important role in all aspects, including in the field of education. This paper describes the use of QR-Code as a digital media in learning German vocabularies. This study used a qualitative approach and was supported by quantitative data. The first data was the use of QR-Code as a digital media to learn German vocabularies in learning process, while the second data was learner's perspective of the learning German vocabularies by using QR-Code. In collecting the data, field note, observation, questionnaire, and documentation were used and the data resulted were in the forms of qualitative and quantitative one. The data were analyzed qualitatively and described descriptively. The data source were students of German as a Foreign Language Program in Universitas Negeri Malang, who attended Deutsch auf B2 Niveau course and were in B1.1 level according to CEFR standard. The study indicates that QR-code can be used as an alternative of digital media to learn German vocabularies. Students were active and anthusiastic about it during the learning process. In addition, students find that the use of this digital media was useful and fun